Are Green Men from Venus? - OBERMILLER, CARL (Archīum Ateneo, 2018)
A consistent finding in sustainability research is that women are eco-friendlier than men, a gap usually ascribed to differences in socialization. Our research explored a corollary process—the cognitive association of environmentalism with femininity along with the consequent negative responses of men that arise from their efforts to safeguard their masculine identity. Two studies replicated the recent discovery (Brough et al., 2016) of a mental association between environmentalism and femininity (for both men and women) and the consequent reduction in the effectiveness of conventional environmental appeals to men. This research also investigated two approaches for overcoming the effects of the implicit association of sustainability with femininity. The first considered that well-learned reflective knowledge structures about advertising or about sustainability might mitigate the resistance of men to environmental appeals. We tested whether established measures of advertising skepticism (Study 1) or sustainability literacy (Studies 1 and 2) would moderate these consequences of the green-feminine association. Whereas skepticism moderated these effects, sustainability literacy did not. The second approach for offsetting the association between sustainability and femininity was to create an environmental appeal with distinctly masculine brand-positioning elements. Two versions of an environmental appeal with different brand elements were produced—one masculine and the other feminine (Study 2). While men and women were equally responsive to the masculine brand positioning, the most positive responses were from women toward the feminine positioning. Collectively, these results corroborate the green-feminine association and demonstrate the moderating role of advertising skepticism. Furthermore, although higher sustainability literacy resulted in more pro-environmental behavior in general, it did not moderate downstream effects of the implicit green-feminine association.